Satellite images and geodetic measurements applied to the monitoring of the Horcones Inferior glacier, Mendoza, Argentina - Lenzano, María Gabriela (2011)
This work analyzes the monitoring of the covered and regenerated Horcones Inferior Glacier (HIG) since the implementation of a semi-permanent GNSS station (HISS) on its surface during the summer seasons of 2009 and 2010. The glacier is located at 32° 41’s and 69° 57’w, at the foot of the south wall of Mt. Aconcagua, Aconcagua Provincial Park, Mendoza, Argentina. The average velocities obtained from the HISS station were of 1.3 cm/d and 3.5 cm/d during the 2009 and 2010 seasons respectively. The data procured using satellite images during the last surges (1984 and 2003) gave average velocities for the HIG front of 8.7 m/d for the first event and 11.5 m/d for the second one. These results allowed getting accurate and reliable movement tendency at the terminal part of the HIG during the 1984-2010 period.